2017
DOI: 10.1097/phm.0000000000000746
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Platelet-Rich Plasma in Pain and Self-Report Function in Knee Osteoarthritis

Abstract: In relieving pain and improving self-report function, PRP showed no superiority over hyaluronic acid in well-designed double-blind trials, and beneficial effects of PRP in most trials probably resulted from insufficient blinding methods. However, PRP is still considered more effective than placebo on the basis of present evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 42 publications
1
41
0
2
Order By: Relevance
“…These results highlight that treatment with PRP works better than HA in patients with OA in terms of relieving pain and improving joint functionality. Prior studies [31][32][33] and several meta-analysis 13,34,35 assessing PRP efficacy revealed PRP to not be better than HA in the context of effectively designed double-blind trials, suggesting the possibility that poor blinding protocols could explain any benefits ascribed to PRP. This is not consistent with our conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…These results highlight that treatment with PRP works better than HA in patients with OA in terms of relieving pain and improving joint functionality. Prior studies [31][32][33] and several meta-analysis 13,34,35 assessing PRP efficacy revealed PRP to not be better than HA in the context of effectively designed double-blind trials, suggesting the possibility that poor blinding protocols could explain any benefits ascribed to PRP. This is not consistent with our conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…While PRP was first used in the 1970s for wound and bone healing in the field of oral and maxillofacial surgery,3 there are now several high-quality systemic reviews, meta-analyses and randomized controlled trails supporting its applications in many fields, including dermatology,4 cardiology,5 plastic surgery,6 orthopedic surgery,7 pain management8 and sports medicine 9 10. As the popularity of this autologous derivative of whole blood grows and it is further studied, the definition of PRP is shifting to be having a minimum platelet concentration of 1 000 000/µL or approximately a fivefold increase in platelets from baseline 11…”
Section: Introductionmentioning
confidence: 99%
“…Cell conditioning procedures can involve gene modifications, treating cells in hypoxia, 3D culture conditions, or addition of cytokines [46]. Interestingly, MSCs obtained from BMC or SVF have different differentiation capabilities to bone and fat but do not differ in their chondrogenic potential [47].…”
Section: Laboratory Expanded Mscsmentioning
confidence: 99%